Clofarabine-induced kidney toxicity. (August 2014) - Jhaveri, Kenar D; Chidella, Shailaja; Allen, Steven L; Fishbane, Steven
Clofarabine is a purine nucleoside analog indicated for treatment of relapsed or refractory acute lymphoblastic leukaemia in children. The drug is also increasingly used, outside of its FDA approved indication, for treatment of relapsed or refractory acute myeloid leukemia in adults. It acts by inhibiting DNA synthesis, the enzyme ribonucleotide reductase and repair and activation of mitochondrial repair processes. We describe a case of a 48-year-old male with refractory acute myeloid leukemia with acute kidney injury associated with clofarabine treatment. We conducted a review of the literature and utilized the Food and Drug Administration Adverse Event Reporting System to identify spontaneous reporting of renal adverse events with this drug in 29 other cases. Since clofarabine inhibits ribonucleotide reductase, we postulate by extrapolation from the animal studies that collapsing glomerulopathy or severe tubular injury or a combination of both may be the mechanism of acute kidney injury observed with this agent. This would be consistent with the observed severe acute kidney injury and proteinuria in humans.